1994
DOI: 10.1080/00288233.1994.9513042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lambing policy and ewe breed cross on wool growth patterns and wool quality

Abstract: The effects of lambing policy (June-or August-lambing) and ewe breed cross on midside patch wool growth and wool quality traits were studied for 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…August-lambing ewes exhibited a more marked variation in wool growth rate during the experimental period than did May-lambing ewes. This is consistent with previous reports that autumnlambing ewes have a more even pattern of wool growth rate (and fibre diameter) than springlambing ewes (Reid et al 1988;Morris et al 1994a). Similarly, the fact that August-born lambs were heavier at birth and at weaning than May-born lambs is consistent with the results of previous studies showing an effect of seasonal lambing policy on lamb birth weights and growth rates to weaning (Reid et al 1988;Obst et al 1991;Morris et al 1993 a,b).…”
Section: Lambing Policysupporting
confidence: 93%
See 2 more Smart Citations
“…August-lambing ewes exhibited a more marked variation in wool growth rate during the experimental period than did May-lambing ewes. This is consistent with previous reports that autumnlambing ewes have a more even pattern of wool growth rate (and fibre diameter) than springlambing ewes (Reid et al 1988;Morris et al 1994a). Similarly, the fact that August-born lambs were heavier at birth and at weaning than May-born lambs is consistent with the results of previous studies showing an effect of seasonal lambing policy on lamb birth weights and growth rates to weaning (Reid et al 1988;Obst et al 1991;Morris et al 1993 a,b).…”
Section: Lambing Policysupporting
confidence: 93%
“…Reid et al (1988) measured greater wool production in autumn-lambing than in spring-lambing ewes during all periods of the year except in September and October when springlambing ewes had a greater wool growth rate. Morris et al (1994a) also reported a greater wool growth rate in spring-lambing ewes compared with winter-lambing ewes during P140-L77 (1.19 versus 0.91 mg/cm 2 per day).…”
Section: Lambing Policymentioning
confidence: 78%
See 1 more Smart Citation
“…Clean yield also varies within sheep flock due to varying amounts of wax and contaminants such as vegetable matter and dirt (Cottle and Baxter, 2015). A similar study conducted in New Zealand found that clean scoured yield proved to be higher for ewes rearing singles as compared to those rearing twins at both shearing's (Morris et al, 1994). The current results indicate that clean yield plays a significant role in the determination of wool price for White wool and Merino wool, all combined.…”
Section: 63supporting
confidence: 54%